Landscapes of Hope : Nature and the Great Migration in Chicago - McCammack, Brian, 1981- (Harvard University Press, 2018)
In the first interdisciplinary history to frame the African American Great Migration as an environmental experience, Brian McCammack travels to Chicago's parks and beaches as well as farms and forests of the rural Midwest, where African Americans retreated to relax and reconnect with southern identities and lifestyles they had left behind.